Bring Me Back - Paris, B. A. (New York St. Martin's Press, 2018)
"She went missing. He moved on. A whole world of secrets remained, until now"--
"She went missing. He moved on. A whole world of secrets remained, until now. Finn and Layla are young, in love, and on vacation. They're driving along the highway when Finn decides to stop at a service station to use the restroom. He hops out of the car, locks the doors behind him, and goes inside. When he returns Layla is gone, never to be seen again. That is the story Finn told to the police. But it is not the whole story. Ten years later Finn is engaged to Layla's sister, Ellen. Their shared grief over what happened to Layla drew them close and now they intend to remain together. Still, there's something about Ellen that Finn has never fully understood. His heart wants to believe that she is the one for him, even though a sixth sense tells him not to trust her. Then, not long before he and Ellen are to be married, Finn gets a phone call. Someone from his past has seen Layla, hiding in plain sight. There are other odd occurrences: Long-lost items from Layla's past that keep turning up around Finn and Ellen's house. Emails from strangers who seem to know too much. Secret messages, clues, warnings. If Layla is alive, and on Finn's trail, what does she want? And how much does she know? A tour de force of psychological suspense, Bring Me Back will have you questioning everything and everyone until its stunning climax."--Jacket flap.
107037
Keywords: Missing persons -- Fiction; Man-woman relationships; Fiction -- Thrillers -- Psychological; Secrecy; Sisters; Suspense fiction; Psychological fiction; Thrillers (Fiction); .